PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP LOYALITAS DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING (STUDI PADA PELANGGAN ROLAG CAFE SURABAYA) - LISTYAN PRATAMA PUTRA, BRILLY (Jurnal Ilmu Manajemen (JIM), 2018)
Rolag cafe is a cafe that was established in 2015 in surabaya with a unique concept that stands on rolag river banks and has complete facilities and prices in accordance with the facilities provided. Rolag cafe always crowded by customers because the facilities provided so complete and the price offered in accordance with the facilities provided. The purpose of this research is to analyze and discuss the influence of service quality and price to loyalty with satisfaction as intervening variable. This type of research is quantitative research. Using non-random sampling technique with the amount of 220 respondents taken from customers Rolag cafe Surabaya. The instrument used is a questionnaire using Likert scale and analyzed by path analysis using AMOS 23. The results showed that there is a positive and significant influence of service quality on loyalty with satisfaction as intervening variable. There is also a positive and significant influence of price on loyalty with satisfaction as intervening variable. In addition there is a positive and significant influence of satisfaction on loyalty. Keywords: SerQuel , Price , satisfaction , loyalty